PEMBELAJARAN DENGAN PENDEKATAN CEP (CHEMO-ENTREPRENEURSHIP) YANG BERVISI SETS (SCEINCE, ENVIRONMENT, TECHNOLOGY AND SOCIETY) GUNA MENINGKATKAN KUALITAS PEMBELAJARAN - Mukhlis Rohmadi (Educatio, 2011)
The purposes of the research are to know : (1) the use of CEP (Chemo-Entrepreneurship) approach with SETS (Science, Environment, Technology, and Society) vision to increase the chemistry cognitive achievement of XIth grade students of science program in Colloid System; (2) the use of CEP (Chemo-Entrepreneurship) approach with SETS (Science, Environment, Technology, and Society) vision to increase the chemistry afective achievement of XIth grade students of science program in Colloid System; (3) the use of CEP (Chemo-Entrepreneurship) approach with SETS (Science, Environment, Technology, and Society) vision to increase the chemistry psychomotoric achievement of XIth grade students of science program in Colloid System;  (4) the use of CEP (Chemo-Entrepreneurship) approach with SETS (Science, Environment, Technology, and Society) vision to increase the students activity of XIth grade students of science program in Colloid System. This research was carried from March 2010 up to April 2011 and used Class Action Research. The research location was concluded MA PPMI Assalaam Sukoharjo. The research subject was entire of students at classes XI Science program  MA PPMI Assalaam that consisted of 2 classes, that was XI IPA 1 and XI IPA 2. Data was collected with tes method, observation, inquiry, interview and documentation. From the data analysis result can be concluded that : (1) first cycle is not yet fulfil designed target from the research, that is reached â‰¥ 70% of students completed learn with get achievement of cognitive â‰¥ 65% and â‰¥ 75% for afective and psicomotor; reached â‰¥ 70% of students active at the learning proccess. The result of first cycle is 80,55% for afective, 71,52% for psychomotor, 64,76% for cognitive and 61,11% for active students. This result shows that learning proccess  from the first cycle is not success; (2) second cycle is fulfil supposed target from the research, that is reached â‰¥ 75% of students completed learn with get achievement of cognitive â‰¥ 70% and â‰¥ 75% for afective and psicomotor; reached â‰¥ 80% of students active at the learning proccess. The result of second cycle is 88,89% for afective, 76,83% for psychomotor, 75,51% for cognitive and 90,97% for active students. This result shows that learning proccess from the second cycle is successfully, so that research is stoped.